2016
DOI: 10.1080/1354750x.2016.1201530
|View full text |Cite
|
Sign up to set email alerts
|

The potential biomarkers of drug addiction: proteomic and metabolomics challenges

Abstract: Drug addiction places a significant burden on society and individuals. Proteomics and metabolomics approaches pave the road for searching potential biomarkers to assist the diagnosis and treatment. This review summarized putative drug addiction-related biomarkers in proteomics and metabolomics studies and discussed challenges and prospects in future studies. Alterations of several hundred proteins and metabolites were reported when exposure to abused drug, which enriched in energy metabolism, oxidative stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
(50 reference statements)
0
15
0
1
Order By: Relevance
“…13 So far, few studies have focused on drugs of abuse (DOA) [14][15][16][17][18] and many of those were performed on mice and rats. Biomarker research can be used for acute or chronic drug consumption to investigate consumption behavior or to find underlying toxicological aspects of its action in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 So far, few studies have focused on drugs of abuse (DOA) [14][15][16][17][18] and many of those were performed on mice and rats. Biomarker research can be used for acute or chronic drug consumption to investigate consumption behavior or to find underlying toxicological aspects of its action in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Biomarker research can be used for acute or chronic drug consumption to investigate consumption behavior or to find underlying toxicological aspects of its action in humans. 13 So far, few studies have focused on drugs of abuse (DOA) [14][15][16][17][18] and many of those were performed on mice and rats. [19][20][21][22] Metabolites such as 5-oxoproline, saccharic acid, uracil, and others showed to be indicative of methamphetamine intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…For the estimation of the postmortem interval (PMI), metabolomics studies found elevated levels of amino acids and creatinine postmortem (Castillo-Peinado and Luque de Castro, 2016) and decreasing levels of sterol sulfates and very-long-chain fatty acids within the postmortem period (Wood and Shirley, 2014). Additionally, biomarker research within the field of forensic toxicology might successfully be used to investigate consumption behavior, to distinguish between acute or chronic drug consumption or to find the underlying mode of toxicological action in humans (Wang et al, 2016a). Thereby, different applications of metabolomics strategies in biomarker research for DOA identification were proposed: (a) as an additional tool for metabolism studies bearing the major advantage that particularly a priori unknown or unexpected metabolites can be identified; and (b) for identification of endogenous biomarker or metabolite patterns, e.g., for synthetic cannabinoids or also to indirectly detect urine manipulation attempts such as artificial urine samples or chemical adulteration.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Metabolomics was probably the last "-omics" approach to be employed in drug addiction studies. The pioneering metabolomic studies aimed to find plasma metabolites that behave like biomarkers, both in diagnosis or to help understand the processes underlying drug addiction [6,7]. Plasma and urine samples from rats subjected to a CPP paradigm with cocaine, amphetamine and morphine have been analyzed using metabolomics techniques, demonstrating that cocaine affected four metabolites: L-threonine (L-Thr), cysteine, n-propylamine and spermidine.…”
Section: Introductionmentioning
confidence: 99%